Aspects of personal control in explaining inmates' adjustment to prison life - Buško, Vesna (Array, 1999)
The study was aimed to test predictions derived from the models of inmate adjustment to prison based on the concept of personal control. The importance of particular aspects of personal control (objective, expected and perceived controllability) in explaining selected measures of adjustment was analysed on a sample of 343 inmates incarcerated in maximum (N=207) and minimum (N=136) security prisons in Croatia. To examine the differences in measures of depression, psychosomatic symptoms, and aggressive behavior with regard to 3 aspects of personal control the three-way analyses of variance were performed, with age, sentence length, time in prison, and number of convictions taken as covariates. Significant differences in the depression scores were found with reference to all three aspects of personal control. Scores on psychosomatic problems scale differed with regard to expected as well as perceived controllability. Inmates with higher expected controllability (internal locus of control) and higher level of perceived controllability scored somewhat lower on both scales. Differences in aggresive behavior measure were found only with regard to expected possibility of control. However, no two-way or three-way interaction effects were found on either of adjustment measures.